The complementary role of microCT and histopathology in characterizing the natural history of stented arteries. (July 2011) - Vorpahl, Marc; Foerst, Jason R; Kelm, Malte; Kaplan, Aaron V; Virmani, Renu; Ball, Timothy
Microcomputed tomography is an important tool for preclinical vascular imaging, with micron-level resolution. This nondestructive means of imaging allows for rapid collection of 2D and 3D reconstructions to visualize pathologic specimens. Postmortem analysis of stented arteries has yielded significant insights into the 'natural'' history of stented arteries. This article outlines a protocol for ex vivo, postmortem cardiac examination of stented arterial segments with microcomputed tomography followed by histopathologic analysis and highlights the complementary nature of these modalities.